Neuraxial biomechanics, fluid dynamics, and myodural regulation: rethinking management of hypermobility and CNS disorders - Frost, Nicole; Barclay, S. Jade (Frontiers in Neurology, 2024)
Individuals with joint hypermobility and the Ehlers-Danlos Syndromes (EDS) are disproportionately affected by neuraxial dysfunction and Central Nervous System (CNS) disorders: such as Spontaneous Intracranial Hypotension (SIH) due to spinal cerebrospinal fluid (CSF) leaks, Upper Cervical Instability (UCI; including craniocervical or atlantoaxial instability (CCI/AAI)), Occult Tethered Cord Syndrome (TCS), Chiari Malformation (CM) and Idiopathic Intracranial Hypertension (IIH). The neuraxis comprises the parts of the nervous system (brain, nerves, spinal cord) along the craniospinal axis of the body. Neuraxial tissue includes all tissue structures that comprise, support, sheath, and connect along the neuraxis and peripheral nerves. Altered mechanical loading or vascular supply of neural structures can adversely impact neural health and conductivity, with local and remote effects on inflammation, venous congestion, and muscle control. With EDS characterized by altered structure of the connective tissues found throughout the body including the neural system, altered mechanical properties of the central nervous system (CNS) and its surrounding tissue structures are important considerations in the development and diagnostics of these CNS disorders, as well as response to therapeutic interventions. Experts have identified a need for neuraxial curriculum in medical education and hypermobility-adapted treatment approaches in pain management, neurosurgery, anesthesiology, hematology, gastrointestinal surgery, dermatology, cardiology, dentistry, gastroenterology, allergy/immunology, physical therapy, primary care, radiology and emergency medicine. This paper reviews the interactions between neuraxial biomechanics and pathology related to CNS disorders seen commonly with EDS. First, we provide a concise synthesis of the literature on neuraxial kinematics and fluid dynamics. We then discuss the interplay of these biomechanics and their involvement in clinically-relevant diagnoses and overlapping symptom presentations, modeling physiological reasoning to highlight knowledge gaps, support clinical decision-making, improve multidisciplinary management of hypermobility-associated complexity, and add weight to the call for medical education reform.